Lexical And Syntactic Problems In The English- Arabic Translations Of Legal Texts On Migrants And Refugees - Rahabneh, Amani Mohammad Nayef (2024)
The present study investigated lexical and syntactic problems in the English Arabic translations of legal texts on migrants and refugees. In order to analyze these problems, it was compulsory to investigate lexical and syntactic features of legal texts. To analyze these features, three models of translation were adopted: Nord's Model of text analysis (2005), Vinay and Darbelnet (2000), and Catford’s theory of shifts (1965). The application of the Skopos theory facilitated the selection of appropriate translation strategies to convey meaning effectively in the target language by analyzing the extratextual and intratextual factors of the texts. Vinay and Darbelnet’s model provided insights into strategies employed during the translation process, while Catford’s theory shed light on structural differences between English and Arabic. Through a descriptive qualitative and quantitative analysis, the study identified lexical and syntactic gaps between English and Arabic legal texts, prompting translators to utilize strategies such as direct translation, transposition, modulation, equivalence, as well as structure shifts, unit shifts, and level shifts. The findings underscored the significant challenges posed by lexical and syntactic features in legal translation. Lexically, there were gaps between the languages, requiring careful consideration of legal terminology and concepts. For example, technical terms are prominently featured. Performative verbs lost a part of their meaning which is obligation or permission